Running against the schedule: are children exercising at the right time? A comment on the Portuguese education system - Ana Maria Abreu; Isolina Frade (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2020)
Introduction: We have all pondered on the physical and emotional benefits of exercise and more often than not, we find ourselves associating exercise to health and wellbeing. However, recent scientific developments have brought into light several benefits of exercise that had not yet been addressed by the scientific community before. The benefits of exercise that reach beyond physical and mental wellbeing such as benefits for the brain and, more specifically, for cognition, attention, and executive functions are now under close investigation. Aim: These new insights render the education community powerful, as we have the tools to better our education system by simply applying these insights to benefit the learning process of our children. Materials and Methods: Here we explore the International success tales on the optimization of the benefits derived from physical exercise. In a pilot study, we investigated 219 schedules from 8 Secondary Schools in Greater Lisbon, and questioned teachers about their insights on learning and behavior in pre-theoretical disciplines Physical Education versus post-theoretical disciplines Physical Education. Results: Portuguese Schools seem to favor afternoon scheduling of Physical Education and the perceptions of teachers seem to point to Physical Education as an obstacle to the learning process of more theoretical disciplines. Conclusion: The international success tales show the importance of physical activity in the morning and clear learning benefits for more theoretical disciplines. Hence, we seek to explore these success tales, while discussing how the Portuguese Education System, but also each educational community, should emulate other countries that have put this newly obtained knowledge into practice.